Jews and theatre in an intercultural context - Nahshon, Edna (Brill's series in Jewish studies, 2012)
Preface -- Religion and origins. Angel, she-ass, prophet: the play and its set-design / Simon Levy -- From Alexandria to Berlin: the Hellenistic play Exagoge joins the Jewish canon / Sarit Cofman-Simhon -- La Pasion de Jesus en Tafi: the representation of Jews in a contemporary Argentine passion play / Tamara Kohn -- Going against the grain: Jews and passion plays on the American mainstream stage, 1879-1929 / Edna Nahshon -- Plays and playwrights. Conceptions, connotations, and/or actions: the figuration of Jewish characters in Heinar Kipphardt's plays / Matthias Naumann -- Between "I and thou": Buber, expressionism and Ernst Toller's search for community / David Garfinkle -- Holocaust memory in the French-Jewish theater of Jean-Claude Grumberg / Seth L. Wolitz -- Holocaust. Voices from the edge of the abyss: theatrical texts from the Terezin/Theresienstadt Ghetto, 1941-45 / Lisa Peschel -- Apart from the document: Jews and Jewishness in theatre. Of the real / Carol Martin -- Fritz Kortner on the postwar stage: the Jewish actor as a site of memory / Michael Bachman -- Interpretations and reinterpretations. Jews in fashion at the Moscow Art Theater / Laurence Senelick -- Restaging La Juive in a Post-Holocaust context / Hans-Peter Bayerdoerfer -- Contemporary audiences and the infamous 'pound of flesh' in Shakespeare's The merchant of Venice / Melia Bensussan -- The contemporary scene. The joy of breaking taboos: Jews and postwar German theatre / Anat Feinberg -- The relativization of victim and perpetrator in the Hungarian productions of Merchant of Venice and Mein Kampf / Aniko Szucs -- From Purimspiel to Polish masquerade: performing Jewish memory in Tykocin / Brigitte Sion -- Diaspora Disneys: 'Jewface' minstrelsy and 'Jewfacade' display in East-Central Europe and Eurasias / S.I. Salamensky -- From Halakha to Hadassah: queer Jewish performance art / Carol Zemel